Immunological tools for the characterization of the humoral immune response to Mycobacterium bovis infection in African buffaloes (Syncerus caffer) - McFadyen, Ross (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016